Newt A1 cell-derived extracellular vesicles promote mammalian nerve growth - Middleton, Ryan C.; Liao, Ke; Liu, Weixin; de Couto, Geoff; Garcia, Nahuel; Antes, Travis; Wang, Yizhou; Wu, Di; Li, Xinling; Tourtellotte, Warren G.; Marbán, Eduardo (Scientific reports, 2023)
Newts have the extraordinary ability to fully regenerate lost or damaged cardiac, neural and retinal tissues, and even amputated limbs. In contrast, mammals lack these broad regenerative capabilities. While the molecular basis of newts’ regenerative ability is the subject of active study, the underlying paracrine signaling factors involved remain largely uncharacterized. Extracellular vesicles (EVs) play an important role in cell-to-cell communication via EV cargo-mediated regulation of gene expression patterns within the recipient cells. Here, we report that newt myogenic precursor (A1) cells secrete EVs (A1EVs) that contain messenger RNAs associated with early embryonic development, neuronal differentiation, and cell survival. Exposure of rat primary superior cervical ganglion (SCG) neurons to A1EVs increased neurite outgrowth, facilitated by increases in mitochondrial respiration. Canonical pathway analysis pinpointed activation of NGF/ERK5 signaling in SCG neurons exposed to A1EV, which was validated experimentally. Thus, newt EVs drive neurite growth and complexity in mammalian primary neurons.